Inflammatory markers in women with postpartum depressive symptoms. Issue 7 (5th September 2018) - Bränn, Emma; Fransson, Emma; White, Richard A.; Papadopoulos, Fotios C.; Edvinsson, Åsa; Kamali‐Moghaddam, Masood; Cunningham, Janet L.; Sundström‐Poromaa, Inger; Skalkidou, Alkistis
Abstract: Postpartum depression (PPD) is a devastating disorder affecting not only more than 10% of all women giving birth, but also the baby, the family, and the society. Compiling evidence suggests the involvement of the immune system in the pathophysiology of major depression; yet, the immune response in perinatal depression is not as well studied. The aim of this study was to investigate the alterations in peripheral levels of inflammatory biomarkers in 169 Swedish women with and without depressive symptoms according to the Edinburgh postnatal depression scale or the M.I.N.I neuropsychiatric interview at eight weeks postpartum. Among the 70 markers analyzed with multiplex proximity extension assay, five were significantly elevated in women with postpartum depressive symptoms in the adjusted LASSO logistic regression analysis: Tumor necrosis factor ligand superfamily member (TRANCE) (OR‐per 1 SD increase = 1.20), Hepatocyte growth factor (HGF) (OR = 1.17) Interleukin (IL)‐18 (OR = 1.06), Fibroblast growth factor 23 (FGF‐23) (OR = 1.25), and C‐X‐C motif chemokine 1 (CXCL1) (OR 1.11). These results indicate that women with PPD have elevated levels of some inflammatory biomarkers. It is, therefore, plausible that PPD is associated with a compromised adaptability of the immune system.